2018
DOI: 10.1007/s10384-018-0573-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of orthokeratology on axial length elongation in children with myopia: Contralateral comparison study

Abstract: Using a contralateral eye study design, which prevented the influence of potential confounding factors, Effectiveness of the OK lens was proved. Myopic progression within a subject was excellent compared with no intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…In a 2-year study by Santodomingo-Rubido et al [ 16 ] in patients aged 6-12 years, the axial length of patients wearing OK lenses increased by 0.47 mm, less than 0.69 mm in the group wearing frame glasses. The same conclusion was reached by the teams of Lau et al [ 17 ] and Na et al [ 18 ].…”
Section: Discussionsupporting
confidence: 74%
“…In a 2-year study by Santodomingo-Rubido et al [ 16 ] in patients aged 6-12 years, the axial length of patients wearing OK lenses increased by 0.47 mm, less than 0.69 mm in the group wearing frame glasses. The same conclusion was reached by the teams of Lau et al [ 17 ] and Na et al [ 18 ].…”
Section: Discussionsupporting
confidence: 74%
“…Long et al [45] reported that the increase in AL after 1 year was 0.05 ± 0.19 mm in the OK group and 0.34 ± 0.21 mm in the control group; the AL difference had a decrease of 0.29 mm. Na et al [38] also reported a one-year AL increase of 0.07 ± 0.21 mm in the OK group and 0.36 ± 0.23 mm in the control group; the AL difference decreased to 0.29 mm. Whereas, Chen et al [46] reported a difference of 0.42 mm in AL elongation between myopic and nonmyopic eyes after wearing OK lenses for 12 months.…”
Section: Discussionmentioning
confidence: 97%
“…The potential of OK lenses for myopic correction and control has been confirmed by several studies [25, 35-37]. Interestingly, OK lenses have demonstrated a beneficial effect against the progression of anisomyopia [38]. Wearing OK lenses for a long period of time would present a more significant AL difference reduction in children with severe anisometropia [39, 40].…”
Section: Introductionmentioning
confidence: 99%
“…OK lenses are custom-designed rigid contact lenses that reshape the cornea to reduce refractive error. Wearing OK lenses overnight reduces the need for patients to wear contact lenses or spectacles in the daytime [ 26 , 27 , 28 , 29 , 30 ]. However, OK lenses can cause higher-order aberrations and lowered contrast sensitivity [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%